The Impact of Mobile-Assisted Language Learning on English as a Foreign Language Learners’ Vocabulary Learning Attitudes and Self-Regulatory Capacity - Lei, Xiao; Fathi, Jalil; Noorbakhsh, Shabnam; Rahimi, Masoud (Frontiers in Psychology, 2022)
Over the past decades, English as a foreign language (EFL) learning has witnessed a heightened interest in the role of mobile-assisted language learning (MALL) in vocabulary learning. To shed more light on the impact of MALL on vocabulary learning, this study, employing a quantitative longitudinal design, aimed at examining the impact of a MALL programme on 139 EFL learners’ vocabulary learning attitudes and self-regulatory capacity. To this end, this study investigated the latent change score models of the learners’ vocabulary learning attitudes and self-regulatory capacity over time. Over the course of one year, various mobile applications were integrated into the regular English language instruction of the learners. The required data were collected via administering vocabulary learning attitude and self-regulating capacity in vocabulary learning scales. The data were analysed applying latent growth curve modelling to examine the participants’ longitudinal trajectories and patterns of change in the two waves of collected data. The fit indices of the latent change models revealed an increase in both the EFL learners’ vocabulary learning attitudes and their self-regulatory capacity during the one-year MALL programme. The analysis of between-person differences also indicated that changes in both variables were positively correlated.